Standardization of the Alberta infant motor scale in full-term Greek infants: Preliminary results. - Syrengelas, D; Siahanidou, T; Kourlaba, G; Kleisiouni, P; Bakoula, C.; Chrousos, G P (Early Hum Dev, 2010)
BACKGROUND: The Alberta Infant Motor Scale (AIMS) is a norm-referenced test that assesses the spontaneous motor performance of infants from birth through independent walking (0-18 months). This scale has been utilized for clinical and research purposes in various countries, however, whether the initial standardization in Canadian infants is also representative of other countries’ populations has been questioned. AIM: To assess whether the AIMS needs new reference values for Greek infants. METHODS: A cohort of 424 healthy full-term infants (250 boys and 174 girls), aged between 7 days and 18 months, derived from various areas of the Prefecture of Attica and from all socio-economic classes to ensure a true representation, was studied. The AIMS-scores of Greek infants were compared with the norm-referenced values of the original Canadian population reported by Piper and Darrah. RESULTS: The mean AIMS-scores did not differ significantly between Greek and Canadian infants at any age level from birth to 18 months, except for the 2-<3 month of age when higher scores were observed in Greek infants (p=0.02). There was no significant difference in AIMS-values corresponding to the 5th and 90th percentile between Greek and Canadian infants. Inter-rater reliability was excellent in our study population [ICC: 0.99 (95% CI: 0.99-0.99)]. CONCLUSION: In healthy full-term Greek infants, gross motor maturity assessed by the AIMS during the first 18 months of age, seems to follow a similar course to that of Canadian infants.
Keywords: Cohort Studies; Cross-Sectional Studies; Female; Greece; Humans; Infant; Male; Motor Activity; Newborn; Observer Variation; Reproducibility of Results; Walking